Improvement of (001)-oriented diamond p-i-n diode by use of selective grown n+ layer - Kato, Hiromitsu; Makino, Toshiharu; Ogura, Masahiko; Tokuda, Norio; Oyama, Kazuhiro; Takeuchi, Daisuke; Okushi, Hideyo; Yamasaki, Satoshi (Physica status solidi. A, Applications and materials science, 2010)
The contact metallization to n‐type diamond is a key subject for realizing diamond bipolar devices. We have proposed the selective growth technique using the patterned surface morphology and 〈111〉 directional growth, and have achieved the heavily P doping even on (001) diamond. The objective of this research is to demonstrate the availability of this selective grown n+ diamond onto a stack junction diode in order to reduce the series resistance of n‐type layer. The p‐i‐n structure with and without n+ layer were fabricated on (001)‐oriented IIb substrate by plasma‐enhanced chemical vapor deposition (CVD) and conventional lithography technique, and their electrical properties are evaluated by current–voltage and capacitance–voltage measurements. Thanks to the selective grown n+ layer, good diode characters are obtained: (i) a decrease in threshold voltage and (ii) an increase in forward current without any degradation of reverse characteristics. The results clearly indicate that the selective growth technique is useful for fabricating the (001)‐oriented bipolar junction devices.